DAMPAK DEBU VULKANIK LETUSAN GUNUNG SINABUNG TERHADAP KADAR Cu, Pb, DAN B TANAH DI KABUPATEN KARO - Raja Forman Barasa; Abdul Rauf; Mariani Sembiring (Jurnal Agroekoteknologi, 2013)
The Study of Effect Volcanic Ash Eruption of Sinabung Mountain on the Content of Copper, Lead,and Boron of Soils at Karo District. Have been done at six locations using Soils Survey Method onSeptember 2010 until March 2012. Each of site soil sampling were done by purposive sampling attwo depths (0-5 cm and 0-15 cm) with two replications. The results showed that at 0,5-15 mm ofthickness of volcanic ash containt at very low level Copper, content of Boron were moderate, high,and very high and content of Lead was at admitted level at 0-5 cm and 0-15 cm soil depth at somesites at Karo DistrictKeywords: volcanic ash, copper, lead, and boron